Use and perceptions of plastination among medical anatomy educators in the United States. Issue 2 (27th December 2017) - Klaus, Rachel M.; Royer, Danielle F.; Stabio, Maureen E.
Abstract : Traditionally, medical schools have maintained collections of tissues/organs to engage students in anatomy. Such collections are often stored in volatile and toxic preservatives. Plastination is an alternative tissue preservation technique in which polymers replace water and lipids resulting in benign, dry, and anatomically authentic specimens. Plastination is used in medical education internationally; however, its use within U.S. medical schools is not widely discussed in the anatomical literature. This study aimed to determine the knowledge, use, and perceptions of plastination as a teaching tool among U.S. anatomy medical educators. A total of 98 medical anatomy educators who fit inclusion criteria and teach allopathic (MD) students and/or osteopathic (DO) students in the United States completed a national survey, representing 77 medical schools across 37 states. Of these, 100% had heard of plastination, 57% correctly defined plastination, but only 39% currently utilize plastinates for anatomy education. The most frequent explanation for nonuse of plastinates was a preference for the dissection experience, followed by lack of resources and negative past experiences related to durability and quality. A majority (75%) of U.S. medical anatomy educators perceived plastination as a good supplement to, but not a replacement for, cadaveric dissection, 19% indicated no curiosity to use plastination or considered it not useful, and 14% expressed ethical concerns. These findings suggest plastinates are more widely used in the United States than reflected by the literature; however, perceptions regarding their utility indicate a dominant theme for their use to supplement, not replace, cadaveric dissection. Clin. Anat, 2017. © 2017 Wiley Periodicals, Inc.